Perancangan dan Uji Coba Alat Pencetak Pelet Ikan Manual dengan Sistem Tekan: Penelitian - Rifki Khoirulsyah; Muhammad Irwansyah; M.Fitra Ardana; Fuad Anwan Naini; Ihsan Dzulvilano; Novri Bangun Saputra (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Feed is one of the largest cost components in fish farming, accounting for 60–70% of total production costs. Therefore, appropriate technology is needed to assist small-scale fish farmers in producing feed independently. This research aims to design and test a manual fish pellet press with a press system. The research methods included designing a manual mill-based tool, conducting functional trials, and evaluating pellet yields, including production capacity, shape uniformity, and pellet durability in water. The trials were conducted in Perkebunan Bandar Selamat Village, Aek Songsongan District. The results showed that the tool can produce pellets at a capacity of 1–1.5 kg/hour. The resulting pellets have a uniform diameter of ±4 mm, a dense texture, and can withstand water for 10–15 minutes. The tool is relatively inexpensive to manufacture (Rp300,000–Rp500,000) and does not require electricity, making it suitable for use in rural areas. The conclusion of this study is that a manual fish pellet press with a pressing system is effective, economical, and feasible to be adopted to help small-scale fish farmers increase their feed self-sufficiency.